Pengembangan Media Youtube dalam Meningkatkan Kemampuan Berbicara Siswa Pada Pembelajaran Bahasa Arab - Winna Nabillah; Nirzal Sunardi; Azyumardi Ajran (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2023)
The purpose of this research is to find out whether YouTube media can improve the speaking skills of MTs Karya Utama students and to find out the process of developing YouTube media in improving the speaking skills of MTs Karya Utama students in learning Arabic. The type of research used in this research is field research. The research instruments used in this study were observation sheets, questionnaires, and test items. While the data collection methods used in this study were observation, questionnaires, and tests. After the score results are obtained, it can be concluded that Youtube media as Arabic language teaching material is stated to be good or good to use with very good quality. So that students can use it as a learning resource in Arabic lessons.